GEOLOGI DAN HIDROGEOLOGI DAERAH KUMANIS, KOTA SAWAHLUNTO DAN KABUPATEN SIJUNJUNG, PROVINSI SUMATRA BARAT - Ziad, Muhammad
PLTU Ombilin was suspected of disposing fly-ash and bottom-ash (abbreviated as FABA) waste in the landfill location that had not been legally assessed. The concerns of environmental contamination, especially groundwater, was derived from the disposal activities. According to government decree, geological and hydrogeological aspects are one of the requisite factors in determining landfill-location’s properness, including FABA landfill area. Regional geology and hydrogeology reflecting the local condition were two important aspects which were needed to be assessed. Therefore, this study is aimed to identify the geologic and hydrogeological conditions (of the landfill-area and its surroundings), to study the impacts of the current FABA-disposal activities to the groundwater condition and determine the properness of the landfill area legally. Geographically, the research area was located at 696000—705000 mE dan 9931000 — 9937000 mS (UTM projection) comprising an area of 54km2. The study area consists of six geomorphologic units: Tumpuktangah Intrusion Hills, Sarasa Intrusion Hills, Talawi – Parambahan Folded Hills, Bulurotan –Empatkotohilir Graben Hills, Ombilin Alluvial Plain unit, and Tomosu Lake. The mature-geomorphic phase is found in the research area accompanied by rejuvenation in several spots. The research area’s stratigraphy is divided into eight nonformal rock units which were aged from Crataceous to Recent. The sequence, from the oldest to youngest ones, were Granodiorite unit, Porphyritic Rhyolite unit, Claystone I unit, Sandstone I unit, Sandstone II unit, Sandstone III unit, Claystone II unit, and Alluvial Deposit unit. Interpretative folds and interpretative faults are geologic structures found in the area. The first deformation caused by the transtensional regime was interpreted to occur during Eocene, followed by the compressional regime at the end of Eocene. The later deformation caused by the extensional regime during Early Miocene, followed by compressional regime was interpreted to occur during Late Miocene—Pliocene. Aquifers in the research area consist of unconfined aquifer found almost throughout the rock units, and unconfined aquitard in several rock units. Groundwater pH values are between 1.6—8.4 with value of <4 in 8% of the research area. Groundwater possess Total Dissolved Solid (TDS) value ranging from 12.6—24800 mg/L with values of >1000 mg/L in 10% of the research area. TDS anomaly was found in Kumanis and Parambahan (AIC) area and was suspected to be correlated with FABA waste and landfill material. Comparison between government regulation and the analysis concluded that PLTU Ombilin’s FABA landfill area satisfiy one amidst three requirements related to the geologic and hydrogeologic conditions. Data acquired were not sufficient to assess one requirement and the other one does not meet the requirement. Further study is required to determine the unassessable points.